1989
DOI: 10.1093/mutage/4.5.335
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of metabolic activation for four mutagens in a bacterial, fungal and two mammalian cell mutagenesis assays

Abstract: The optimum concentrations of Aroclor-induced rat liver S9 microsomal fraction for the mutagenic activity of the four standard mutagens 2-aminofluorene (2-AF), acriflavine (ACR), benzo[a]pyrene (BP) and cyclophosphamide (CP) were determined in four mutation assays. The four assays were the Ames test using Salmonella typhimurium strain TA100, cycloheximide resistance in the yeast Saccharomyces cerevisiae, the mouse lymphoma TK assay and the human peripheral lymphocyte cytogenetic assay. BP was the only mutagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, a substantial amount of long-term clinical data is available for systematic applications of ACF ( Gama et al., 2020 ; Mathé et al., 1996 , 1998 ), thus alleviating concerns related to the potential mutagenic effects, especially for short-term antiviral therapy. Importantly, the antiviral effects are observed at concentrations of 2–3 orders of magnitude lower than those used in experiments assessing in vitro mutagenicity of ACF ( Obstoy et al., 2015 ; Rees et al., 1989 ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, a substantial amount of long-term clinical data is available for systematic applications of ACF ( Gama et al., 2020 ; Mathé et al., 1996 , 1998 ), thus alleviating concerns related to the potential mutagenic effects, especially for short-term antiviral therapy. Importantly, the antiviral effects are observed at concentrations of 2–3 orders of magnitude lower than those used in experiments assessing in vitro mutagenicity of ACF ( Obstoy et al., 2015 ; Rees et al., 1989 ).…”
Section: Discussionmentioning
confidence: 97%
“…The dendogram revealed that the signature was most similar to non‐genotoxic agents for all three replicates of dexamethasone, but the PCA placed the outlier sample on the borderline between genotoxic and non‐genotoxic agents. Given that one of the three replicates of dexamethasone was classified as genotoxic, and based on the observed cytotoxic effects of S9 and recommendations in the literature for TK6 cells [Rees et al, ; Xiao and Fontanie, ; OECD, ], we advise the use of lower concentrations of S9 when possible to avoid false positives. We thus performed our subsequent experiments using 2% Aroclor‐induced S9.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a substantial amount of long-term clinical data is available for systematic applications (Gama CRB, 2020;Mathé et al, 1996;Mathé et al, 1998), thus alleviating concerns related to the potential mutagenic effects of short-term antiviral therapy. Importantly, the antiviral effects are observed at concentrations of two to three orders of magnitude lower than those used in experiments assessing in vitro mutagenicity of ACF (Obstoy et al, 2015;Rees et al, 1989).…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, the antiviral effects are observed at concentrations of two to three orders of magnitude lower than those used in experiments assessing in vitro mutagenicity of ACF (Obstoy et al, 2015;Rees et al, 1989).…”
Section: Discussionmentioning
confidence: 94%